Use of computed tomography to detect postoperative changes after lichtenstein inguinal hernia repair - Hasbahçeci, Mustafa; Erol, Cengiz (AVES, 2015)
Objective: This study aimed to evaluate the effect of computed tomography to visualize the post-operative changes after Lichtenstein inguinal hernia repair. Methods: Patients with Lichtenstein inguinal hernia repair and post-operative computed tomography scans were included. There were 11 male patients with 14 hernias; the mean age was 63.9±9.2 years. Time interval between inguinal hernia repair and imaging was 186±70 days (median, 211 days). After multiplanar reformatting, images were reviewed with respect to the postoperative changes and visualization of anatomic structures that were found in the inguinal region. Results: The inferior epigastric artery and vein, inguinal ligament, spermatic cord, and pubic tubercle were clearly detected in all the males. Small fluid collections were observed only during early post-operative period in two patients (14.3%). Minimal thickening of the inguinal ligament with fatty streaks and completely normal appearance were present in eight (57%) and six (43%) inguinal regions, respectively. Conclusion: Multiplanar reformatting helps physicians in visualizing the inguinal anatomy in the patients with hernia post surgery. Lichtenstein inguinal hernia repair may be regarded as the gold standard technique for inguinal hernia repair because of the lack of any destructive anatomical changes.

Amaç: Bu çalışmanın amacı Lichtenstein inguinal herni onarımı sonrası oluşan postoperatif değişikliklerin görüntülenmesindeki bilgisayarlı tomografi etkisini değerlendirmektir. Yöntemler: Lichtenstein inguinal herni onarımı yapılan ve postoperatif bilgisayarlı tomografi taraması olan hastalar dahil edildi. Yaş ortalaması 63,9±9,2 yıl olan 11 erkek hastanın toplam 14 fıtık bölgesi vardı. Inguinal herni onarımı ve görüntüleme arasında geçen süre 186±70 gün (ortanca 211 gün) idi. Çok düzlemli yeniden biçimlendirme sonrası, görüntüler postoperatif değişiklikler ve inguinal bölgede bulunan anatomik yapıların görüntü- lenmesi açısından incelendi. Bulgular: İnferior epigastrik arter ve ven, inguinal ligament, spermatik kord ve pubik türkül her hastada net bir şekilde tespit edildi. Küçük sıvı koleksiyonları iki hastada (%14,3) sadece ameliyat sonrası erken dönemde görüldü. Yağlı çizgilenme ile birlikte inguinal ligamentte minimal kalınlaşma ve tamamen normal görünüm sırası ile sekiz (%57) ve altı (%43) inguinal bölgede görüldü. Sonuç: Çok düzlemli yeniden biçimlendirme hekimlere inguinal herni cerrahisi sonrası hastaların inguinal anatomisinin görüntülenmesine yardımcı olur. Lichtenstein inguinal herni onarımı, kalıcı anatomik değişikliklerin olmaması nedeniyle inguinal herni onarımı için altın standart teknik olarak kabul edilebilir.
Lichtenstein inguinal herni onarımı sonrası postoperatif değişikliklerin saptanmasında bilgisayarlı tomografinin kullanımı
Keywords: Inguinal Hernia; Computed Tomography; Lichtenstein Hernia Repair; İnguinal Herni; Bilgisayarlı Tomografi; Lichtenstein Herni Onarımı